The Body in Cognitive Linguistics. Conceptual Metaphor and Embodiment - Gonzalez, Daniela Soledad (2017)
The present work approaches the way in which Cognitive Linguistics addresses the issue of the body in relation to language, which is understood as a correlate of thought. One of the axes of language addressing that characterizes this theoretical approach is the notion of conceptual metaphor postulated by Lakoff and Johnson (2001). These authors conceive metaphor as a phenomenon of thought that is reflected in language, is omnipresent in everyday life and allows the structuring of experience. The experience to which they refer is essentially corporal. The influence of body experience in conceptualizing is called embodiment or embodied mind (Lakoff, 1987: 12).